Analysis of Underage Marriage Impacting Broken Homes and Domestic Violence - Muchtarom, Muchtarom; Imraan , Mohd (PDPI (Perkumpulan Dosen Peneliti Indonesia), 2024)
The objectives of this research are 1. To determine the factors that cause underage marriage. 2. To determine the impact of underage marriage on acts of domestic violence and Broken Homes. 3. To find out the steps in dealing with underage marriage. Research method with a qualitative approach. Observational data collection techniques, the compiler directly goes into the field (2). Interviews, using direct dialogue with several elements of society such as Religious Affairs Office Officers and Religious Figures. Documentation, namely collecting data from documents such as archives and related files. Conclusion The factors that cause underage marriage in Bandung Regency are economic factors, pregnancy out of wedlock, lack of awareness about the importance of education, shame factors, environmental factors, and promiscuity factors. The impact of child marriage on Broken Homes and domestic violence. This can be seen from several phenomena that occur in Bandung Regency